Physical Compatibility of Intravenous Drugs Commonly Used in Intensive Care Units: An Observational Study and Physical Compatibility Laboratory Tests on Anti-Infective Drugs - D'Huart Elise; Vigneron Jean; Demoré Béatrice (De Gruyter, 2019)
The objectives were to perform an observation of the administration of injectable drugs in three ICUs, to identify injectable drugs administered by Y-site infusion or mixed in the same container, to compare with physical compatibility data available in the literature and to test the physical compatibility for missing data.